2021
DOI: 10.3390/ijerph18030930
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Objective and Subjective Housing Status with Individual Mental Health in Guangzhou, China

Abstract: Housing is an important social determinant of mental health. However, few studies simultaneously measure the objective housing status (i.e., housing tenure, living space, housing conditions, and housing stability) and subjective housing status (i.e., housing satisfaction) as well as examine their effects on people’s mental health (i.e., stress, anxiety, and depression). Thus, using a sample size of 1003 participants by two-stage random sampling survey in Guangzhou, China, this study applies multivariate ordina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
3
2
0
Order By: Relevance
“…The Chi-squared analysis suggests that respondents who lived with family or friends had a higher prevalence of likely MDD compared to respondents with other housing characteristics. This result is consistent with an earlier study that found a higher prevalence of mental health problems such as depression due to conflicts between family members and friends living together during the COVID-19 pandemic [ 71 ]. This may be due to misunderstandings over whether or how family members and friends should protect themselves against the virus and the differences in opinions related to the conflicting information about the COVID-19 pandemic [ 71 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The Chi-squared analysis suggests that respondents who lived with family or friends had a higher prevalence of likely MDD compared to respondents with other housing characteristics. This result is consistent with an earlier study that found a higher prevalence of mental health problems such as depression due to conflicts between family members and friends living together during the COVID-19 pandemic [ 71 ]. This may be due to misunderstandings over whether or how family members and friends should protect themselves against the virus and the differences in opinions related to the conflicting information about the COVID-19 pandemic [ 71 ].…”
Section: Discussionsupporting
confidence: 93%
“…This result is consistent with an earlier study that found a higher prevalence of mental health problems such as depression due to conflicts between family members and friends living together during the COVID-19 pandemic [ 71 ]. This may be due to misunderstandings over whether or how family members and friends should protect themselves against the virus and the differences in opinions related to the conflicting information about the COVID-19 pandemic [ 71 ]. In another study, adequacy of living space, housing stability and housing satisfaction were significantly associated with a high prevalence of depression [ 72 ].…”
Section: Discussionsupporting
confidence: 93%
“…Noteworthy, a house is a crucial family asset and is regarded as a potent status symbol in China ( 70 ). This study found that better housing conditions were inversely associated with psychological stress, consistent with previous studies, showing that inadequate housing conditions are associated with worsening mental health (i.e., stress, anxiety, and depression) ( 71 73 ). Although pathways have been proposed to elucidate this association, future studies are required to validate the role of the other specific urbanization elements in improving psychological outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…Inadequate, low quality, living space is associated with poorer mental health (Xie et al, 2021) and this relationship may be more pronounced at times of transition (Foye, 2017), such as the COVID-19 lockdown. Conversely, access to high-quality outdoor spaces, especially “green” spaces, has been associated with stress reduction (Ulrich et al, 1991), and increased well-being (White et al, 2019).…”
Section: Parenting and Child Developmentmentioning
confidence: 99%